Facile fabrication of superhydrophobic meshes with different water adhesion and their influence on oil/water separation. Issue 93 (21st September 2016) - Li, Jian; Kang, Ruimei; Zhang, Yan; Li, Mouji; She, Houde; Zha, Fei; Lei, Ziqiang
Abstract : The water adhesion of superhydrophobic meshes has nearly no effect on their separation efficiency. Abstract : The control of water adhesion is important for superhydrophobic surfaces in numerous applications. Compared with the abundant research on oil/water separation through the use of superhydrophobic materials, research relating to the influence of the water adhesion of superhydrophobic materials on their oil/water separation performance is extremely rare. Herein, superhydrophobic ZnO coated meshes with different water adhesion were successfully prepared by spraying ZnO nanoparticles (NPs) on a stainless steel mesh. By simply changing the percentage of hydrophobic ZnO NPs in the hydrophobic/hydrophilic ZnO NP mixture, superhydrophobic ZnO meshes with different water adhesion have been fabricated successfully. In addition, the separation mechanism for oil/water mixtures is elaborated by interpreting the different states of a water droplet on the surface before and during separation. Furthermore, the influence of the water adhesive property of superhydrophobic meshes on their oil/water separation performance is studied. To the best of our knowledge, this issue has scarcely been considered. It is found that the influence of the adhesive property of the superhydrophobic meshes on their oil/water separation performance can be neglected. The superhydrophobic ZnO coated meshes whether with low or high water adhesion showed nearly the same separation efficiency, which is up to 98.5% for a kerosene and water mixture. The water intrusion pressure and oil flux study exhibit that the low adhesive meshes show a little higher water intrusion pressure and oil flux than the high adhesive meshes. This report assesses the influence of the water adhesion of superhydrophobic materials on their oil/water separation performance, which not only helps us to further understand the mechanism of oil/water separation, but also to design and prepare superhydrophobic surfaces for the effective separation of water from oil.